2022
DOI: 10.3390/immuno2010014
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis in Cancer Immunotherapy—Implications for Hepatocellular Carcinoma

Abstract: Ferroptosis is a recently recognized iron-dependent form of non-apoptotic regulated cell death (RCD) characterized by lipid peroxide accumulation to lethal levels. Cancer cells, which show an increased iron dependency to enable rapid growth, seem vulnerable to ferroptosis. There is also increasing evidence that ferroptosis might be immunogenic and therefore could synergize with immunotherapies. Hepatocellular carcinoma (HCC) is the most common primary liver tumor with a low survival rate due to frequent recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 244 publications
(296 reference statements)
0
9
0
Order By: Relevance
“…Given that T cells are critical mediators of antitumor immunity, ferroptosis has recently been demonstrated to participate in ICIs (e.g., anti-PD-1 or anti-CTLA4)-mediated antitumor immune responses driven by cytotoxic T cells. INF-γ that is secreted from the activated cytotoxic CD8 + T cells upon ICIs blockade enhances ferroptotic effect on tumor cells by downregulating the expression of cysteine/glutamate transporter (system X C − ) subunits, SLC3A2 and SLC7A11, leading to reduced cystine uptake and subsequently enhanced lipid peroxidation and ferroptosis of the cancer cells [ 111 , 121 , 122 ] ( Figure 4 ).…”
Section: Ferroptosis Initiating Therapies (Fits) As the Achilles Heel...mentioning
confidence: 99%
See 4 more Smart Citations
“…Given that T cells are critical mediators of antitumor immunity, ferroptosis has recently been demonstrated to participate in ICIs (e.g., anti-PD-1 or anti-CTLA4)-mediated antitumor immune responses driven by cytotoxic T cells. INF-γ that is secreted from the activated cytotoxic CD8 + T cells upon ICIs blockade enhances ferroptotic effect on tumor cells by downregulating the expression of cysteine/glutamate transporter (system X C − ) subunits, SLC3A2 and SLC7A11, leading to reduced cystine uptake and subsequently enhanced lipid peroxidation and ferroptosis of the cancer cells [ 111 , 121 , 122 ] ( Figure 4 ).…”
Section: Ferroptosis Initiating Therapies (Fits) As the Achilles Heel...mentioning
confidence: 99%
“…Nonetheless, ferroptosis in immune cells themselves may compromise the immune responses, and there is considerable controversy as to whether ferroptosis is a two-edged sword. It has been aware that GPX4 activity is not only important for the survival of tumor cells but also plays an essential role in the development of lymphocytes [ 122 , 123 ]. Further works on T cells have revealed that deficiency of GPX4 in antigen-specific CD4 + and CD8 + T cells are unable to expand and experience ferroptotic cell death induction with an accumulation of lipid peroxides, thereby precluding their immune response to protect the host from infections [ 114 , 123 ].…”
Section: Ferroptosis Initiating Therapies (Fits) As the Achilles Heel...mentioning
confidence: 99%
See 3 more Smart Citations